KARAKTERISASI MORFOLOGIS BETTA EDITHAE YANG TERDAPAT DI KABUPATEN BANGKA TENGAH DAN KABUPATEN BANGKA SELATAN - Prananda, Mustobi; Hafidz, Agus M; Kanaah, Akhlakul; Syarif, Ahmad Fahrul (Program Studi Akuakultur, Universitas Bangka Belitung, 2024)
Betta edithae is one of the native freshwater fish species found on Bangka Island. This species has the potential to be developed as an ornamental fish because it has a unique and attractive body shape. However, its presence in nature is currently threatened by environmental degradation, habitat loss or change, introduction of foreign fish and overexploitation. The existence of Betta edithae species in Bangka Island, especially in Central Bangka and South Bangka districts, has never been reported scientifically. Therefore, the description of Betta edithae species in Central Bangka Regency and South Bangka Regency needs to be analyzed based on morphological aspects. This study aims to determine the morphological characteristics of Betta edithae species found in Central Bangka and South Bangka. The research method was carried out qualitatively with an exploratory descriptive approach. The results of the study show that the morphological characterization of Betta edithae found in Central Bangka and South Bangka districts shows that both fish have the same morphology. Morphometric character measurements of Betta edithae fish found in Central Bangka and South Bangka show that Betta edithae fish found in Central Bangka have a total length of 4.36 cm, which is greater than Betta edithae found in South Bangka. The meristic characters of Betta edithae fish found in the Central Bangka district are D.I.8, A.23, P.8, V.I.4, C.12. The meristic characters of Betta edithae fish found in South Bangka district are D.I.7, A.23, P.6, V.1.4, C.12.